EVIDENCE-BASED OF PAIN MANAGEMENT IN POSTOPERATIVE PATIENTS A CASE STUDY - -, Chanif (Jurnal Keperawatan Medikal Bedah, 2013)
Pain is the main reason encountered by hospitalized patients in general and surgical patients in particular. Postoperative pain is caused by tissue damage as a consequence of the surgical procedure. Nurse has role to control and relieve of acute postoperative pain. This study aim to describe the level of acute postoperative pain and influencing factors among the surgical patients, and evaluate the outcomes of evidence based practice interventions in relieving acute postoperative pain. Four patients who underwent surgery, cooperative, able to communicate and follow up for at least three days were selected as a subject. The DDQ and NRS were used to collect the data. The findings showed that the pain score decreased after subject received pain management intervention both pharmacologic and nonpharmacologic. Pain medication alone is not effective; they need non-pharmacologic approach as well. This study recommended both pain management pharmacologic and non-pharmacologic can be used together in relieving acute postoperative pain. To improve of knowledge, in clinical setting particularly in surgical ward, nurses have to try to apply the evidence based in managing pain.